About Projections of Solutions for Fuzzy Differential Equations - Moiseis S. Cecconello; Jefferson Leite; Rodney C. Bassanezi; Joao de Deus M. Silva (Journal of Applied Mathematics)
In this paper we propose the concept of fuzzy projections on subspaces of , obtained from Zadeh's extension of canonical projections in , and we study some of the main properties of such projections. Furthermore, we will review some properties of fuzzy projection solution of fuzzy differential equations. As we will see, the concept of fuzzy projection can be interesting for the graphical representation of fuzzy solutions.